Chromosomal location of heterochromatin and 45S rDNA sites in four South American triatomines (Heteroptera:Reduviidae) - Bardella, V. B. [UNESP]; Gaeta, M. L.; Vanzela, A. L.L.; Azeredo-Oliveira, M. T.V. [UNESP] (Pensoft Publishers, 2010)
The Triatominae are distributed in Brazilian regions and are the vector of Chagas disease. This group is also characterized by lower karyotype variability, occurrence of holokinetic chromosomes and inverted meiosis of the sex chromosomes. In this study, we determined the karyotype of four species of the genus Triatoma Laporte, 1832 using chromosome measurement, chromosome banding and FISH with a 45S rDNA probe. All samples showed 2n = 20A+XY with chromosomes sorted by size in decreasing order. Heterochromatin of Triatoma infestans melanosoma Lent, Jurberg, Galvão, Carcavallo, 1994 is distributed among eight autosomes and the sex chromosomes. In Triatoma brasiliensis Neiva, 1911, T. matogrossensis Leite, Barbosa, 1953 and T. rubrovaria Blanchard, 1834, heterochromatin was restricted to the Y chromosome, which was characterized as DAPI+ (weak signal). FISH using a 45S rDNA probe of Drosophila melanogaster Meigen, 1830 showed differences in the number and location of hybridization sites. T. brasiliensis and T. rubrovaria showed the signal on one autosome pair. T. matogrossensis showed signals on both sex chromosomes, and T. infestans melanosoma only on the X chromosome. Conventional banding analysis suggests a closer relationship between T. brasiliensis, T. matogrossensis and T. rubrovaria, except with regard to 45S rDNA location in T. matogrossensis, and a more differentiated karyotype in T. infestans melanosoma. © Comparative Cytogenetics.
Keywords: 45S rDNA; Fish; Holokinetic chromosomes; Repetitive DNA; Triatoma